Economic Empowerment of Tribes through Non-Timber Forest Products (NTFPs) in Chhattisgarh State - Ashish Kumar Gupta, M.L. Sharma; S. Limje (Indian Journal of Extension Education, 2023)
The present study was carried out in Bilaspur district of Chhattisgarh in the year 2014-2015. For this purpose 135 NTFPs collecting tribes were selected as a respondent. The findings of the study indicated that out of 24 collected NTFPs 16 NTFPs were available in the month of April to June. 100.00 per cent of them were involved in collection of mahua. Selling of such NTFPs had generates total income of Rs. 1246929.14 annually to all sample households. Among these NTFPs maximum economic contribution came from mahua. It was also found that maximum per family normal employment generated from mahua collection. Majority of the respondents (88.89%) were got annually 75 to 150 days of overall normal employment from the collection of such NTFPs. Correlation analysis describes that out of 11 variable only 5 variables were significantly correlated with employment generation by NTFPs either at 0.05 or at 0.01 level of probability. In this study it was observed that NTFPs play a significant role in the economic empowerment of the tribes by providing them almost year round income and employment.